2008
DOI: 10.1007/s11095-008-9706-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using a Bone-Targeted, Macromolecular Delivery System Coupled with Prostaglandin E1 to Promote Bone Formation in Aged, Estrogen-Deficient Rats

Abstract: Purpose Macromolecular delivery systems have therapeutic uses because of their ability to deliver and release drugs to specific tissues. The uptake and localization of HPMA copolymers using Asp8 as the bone-targeting moiety was determined in aged, ovariectomized (ovx) rats. PGE1 was attached via a cathepsin K-sensitive linkage to HPMA copolymer–Asp8 conjugate and was tested to determine if it could promote bone formation. Materials and Methods The uptake of FITC-labeled HPMA copolymer–Asp8 conjugate (P-Asp8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…Therefore, ALN has been conjugated to some biological/synthetic polymers as drug carriers to endow them with the special HAP binding ability to develop bone- or tooth-targeted drug delivery systems414243444546. In this study, ALN was conjugated to CMC to form CMC-ALN; the introduction of ALN did not affect the stabilizing ability of CMC.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, ALN has been conjugated to some biological/synthetic polymers as drug carriers to endow them with the special HAP binding ability to develop bone- or tooth-targeted drug delivery systems414243444546. In this study, ALN was conjugated to CMC to form CMC-ALN; the introduction of ALN did not affect the stabilizing ability of CMC.…”
Section: Discussionmentioning
confidence: 93%
“…Various tetracyclines and bisphosphonates have been frequently used as bone-targeting moieties in nanotechnology-based therapy, but limitations related to these drugs remain. 15,16 Tetracycline binds mainly with less-crystalline hydroxyapatites (newly forming bone), 17 and long-term use of bisphosphonate increases the risk of osteonecrosis in the jaw. 18 A short peptide sequence of repetitive aspartic acid (4-10 amino acids) has been shown to interact exclusively with bone in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Bringing targeting via ionic interactions full circle, Miller et al demonstrated using fluorescence microscopy that tetracycline deposits preferentially onto growing surfaces, or those with low crystallinity (Fig. 6) [59]. Application of these principles means that targeting osteoclasts should be done with AOs, which prefer absorbing surfaces, while targeting osteoblast should be done with tetracycline, which prefers growing surfaces of bone.…”
Section: Targetingmentioning
confidence: 99%
“…The unstable carbamic acid rapidly releases carbon dioxide and yields the unmodified drug [78,79]. Use of such spacers was shown in bone-targeted delivery of PGE 1 [59] and anticancer drugs to bone [80-82]. …”
Section: Polymer Carriersmentioning
confidence: 99%
See 1 more Smart Citation